1991
DOI: 10.1159/000125979
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in the Rat Arcuate Nucleus Are Hyperpolarized by GABA<sub>B</sub> and μ-Opioid Receptor Agonists: Evidence for Convergence at a Ligand-Gated Potassium Conductance

Abstract: Both γ-aminobutyric acid (GABA) and the endogenous opioid peptides have pervasive effects on neuroendocrine function. This study examined the effects of selective activation of GABAB and/or µ-opioid receptors on neurons of the arcuate nucelus (ARC) of the rat hypothalamus using intracellular recording of cells in a hypothalamic slice. Some recorded neurons were filled with biocytin allowing subsequent identification and immunocytochemical evaluation for the presence of β-endorphin. ARC neurons exhibited a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 22 publications
(28 reference statements)
9
33
0
Order By: Relevance
“…OFQ has recently been shown to activate a K¤ conductance in guinea-pig arcuate neurones (Wagner et al 1998), an effect similar to that reported earlier for DAMGO in arcuate neurones of the guinea-pig and rat (Loose & Kelly, 1990;Loose et al 1991). In the rat arcuate nucleus, application of OFQ (100-1000 nÒ) was found to activate an outward current (13·0 ± 1·5 pA, 43 of 78 cells) (Fig.…”
Section: Postsynaptic Modulation Of Hypothalamic Neuronessupporting
confidence: 85%
“…OFQ has recently been shown to activate a K¤ conductance in guinea-pig arcuate neurones (Wagner et al 1998), an effect similar to that reported earlier for DAMGO in arcuate neurones of the guinea-pig and rat (Loose & Kelly, 1990;Loose et al 1991). In the rat arcuate nucleus, application of OFQ (100-1000 nÒ) was found to activate an outward current (13·0 ± 1·5 pA, 43 of 78 cells) (Fig.…”
Section: Postsynaptic Modulation Of Hypothalamic Neuronessupporting
confidence: 85%
“…It should be noted, however, that incubation time with insulin in previous studies was much shorter than in this study, and more detailed exploration of the possible involvement of GABA A receptor-mediated signaling in the insulin action on NPY gene expression is warranted. Approximately half of the neurons in the hypothalamus are GABAergic in vivo (Decavel and van den Pol, 1990), and GABA is shown to hyperpolarize most neurons in the arcuate nucleus (Loose et al, 1991;Wagner et al, 1998). In this study, we demonstrated that, as in vivo (Wisden et al, 1992;Schwartz et al, 1993;Kaupmann et al, 1997), GABA receptors are expressed in the hypothalamic slices and that most NPY neurons in the arcuate nucleus expressed GAD mRNA.…”
Section: Discussionsupporting
confidence: 49%
“…We therefore hypothesized that an elevation in serum estrogens plays a role in modifying the opioidergic tone through a modification of the receptor-mediated response in parvocellular neurosecretory neurons (e.g., P-endorphin, dopamine, and gonadotropin-releasing hormone). Since GABA is another potent inhibitory transmitter in the hypothalamus that is present in the ARC (Vincent et al, 1982) and the GABA, receptor is coupled to the same inwardly rectifying potassium conductance in the rat (Loose et al, 1991), we tested the hypothesis that estrogen suppresses both the p-opioid and GABA, responses that are coupled to the inwardly rectifying K+ channel. The EC,, values for the p-opioidand the GABA,-mediated hyperpolarization were compared in slices obtained from female guinea pigs exposed to low levels of serum estrogen versus high levels of serum estrogen.…”
Section: Morphinementioning
confidence: 99%